Development of a plant-based oral vaccine candidate against the bovine respiratory pathogen Mannheimia haemolytica - Kaldis, Angelo; Uddin, Muhammed Salah; Guluarte, Jose Ortiz; Martin, Coby; Alexander, Trevor W.; Menassa, Rima (Frontiers in Plant Science, 2023)
Bovine respiratory disease (BRD) affects feedlot cattle across North America, resulting in economic losses due to animal treatment and reduced performance. In an effort to develop a vaccine candidate targeting a primary bacterial agent contributing to BRD, we produced a tripartite antigen consisting of segments of the virulence factor Leukotoxin A (LktA) and lipoprotein PlpE from Mannheimia haemolytica, fused to a cholera toxin mucosal adjuvant (CTB). This recombinant subunit vaccine candidate was expressed in the leaves of Nicotiana benthamiana plants, with accumulation tested in five subcellular compartments. The recombinant protein was found to accumulate highest in the endoplasmic reticulum, but targeting to the chloroplast was employed for scaling up production due the absence of post-translational modification while still producing feasible levels. Leaves were freeze dried, then orally administered to mice to determine its immunogenicity. Sera from mice immunized with leaf tissue expressing the recombinant antigen contained IgG antibodies, specifically recognizing both LktA and PlpE. These mice also had a mucosal immune response to the CTB+LktA+PlpE protein as measured by the presence of LktA- and PlpE-specific IgA antibodies in lung and fecal material. Moreover, the antigen remained stable at room temperature with limited deterioration for up to one year when stored as lyophilized plant material. This study demonstrated that a recombinant antigen expressed in plant tissue elicited both humoral and mucosal immune responses when fed to mice, and warrants evaluation in cattle.